The potential role of university community engagement in supporting transformative social innovation – experiences from Hungary. - Málovics, György; Bajmócy, Zoltán; Csernák, Janka; Fehér, Bori; Frigyik, Márta; Juhász, Judit; Matolay, Réka; Müllner, András; Szerencsés, Rita (Innovation: The European Journal of Social Sciences, 2025)
University community engagement (UCE) is the cooperation between academic actors and marginalized, resource-poor community stakeholders in ways that are mutually beneficial to both parties. The goal of such partnerships is to tackle social exclusion and injustice and to foster environmental sustainability. Such an approach shows remarkable similarities with social innovation (SI), which also denotes bottom-up processes, with CSO involvement aimed at responding to community needs. The present paper aims to analyse the relationship between these two concepts: the role UCE can play in transformative SI (TSI). We approach this topic by the empirical analysis of four initiatives in Hungary, in which universities or their specific units institutionalized UCE as a result of bottom-up processes. To reflect on these cases, we utilize the 'TRANSIT model' of SI, which is a relational framework developed to understand how SI processes contribute to transformative change. Our conclusion is that although the diverse practices of UCE contribute to emergence and diffusion of SI in multiple ways, a number of structural and contextual limitations can be identified with regard to UCE's contributions to TSI. Despite the recognition of these limitations, promoting the expansion of UCE may still play a role in the fostering of TSI processes.